Disclosure Quality Rankings and Stock Misvaluation – Evidence from Chinese Stock Market. Issue 14 (13th November 2020) - Yang, Zhu; Ho, Kung-Cheng; Shen, Xixi; Shi, Lisi
ABSTRACT: Using SZSE's disclosure rankings data, this paper studies the relation between firms' disclosure quality and stock mispricing in emerging markets. We find that higher disclosure ranking grades, the proxy for disclosure quality, is associated with less stock misvaluation in the sense that market price deviates less from its fundamental. We also investigate the variation in this relation across industries and time. Our results document that the association between disclosure ranking grades and stock misvaluation is stronger for firms in more competitive industries. This finding suggests that higher disclosure ranking grades help draw more investors' attention, which will reinforce the role of corporate disclosure in reducing stock misvaluation. In addition, increase in disclosure ranking grades is more effective in reducing stock misvaluation in years prior to China's Split Share Structure Reform (SSSR), which is consistent with our conjecture that corporate disclosure is more valuable in promoting pricing efficiency when private information collection activities are less active.